A novel power-on-reset circuit for passive UHF RFID tag chip *Project supported by the Key Laboratory of Agricultural Informatization Standardization, Ministry of Agriculture and Rural Affairs. (December 2018) - Wang, Ang; Yu, Lina; Wu, Dehua; Fu, Shibo; Gao, Wanlin; Xiao, Wan'ang
Abstract: A novel power-on-reset (POR) circuit with simple architecture, small values of capacitances, ultra-lower power consumption, and self-adjustable delay time of reset pulse for passive UHF RFID tags is presented in this paper. A proposed delay element was adopted for the features of small capacitances and wide power supply rise time range. An inverter was used as a two-inputs logic device to simplify the architecture of the circuit. The technology used for design and simulation is SMIC 0.18 μ m RF. Simulation results show that the circuit functions well under different process corners with different power supply rise time, and is able to generate a POR signal after the power supply is briefly powered off. The static power consumption is less than 30 pA. Moreover, the circuit operates properly along with other modules of analog front-end.